Neuropsychological Impairments in Young Patients With Subclinical Hypothyroidism: A Case Control Study. Issue 3 (July 2020) - Kalra, Pramila; Kumaraswamy, D. R.; Dharmalingam, Mala; Saini, Jitender; Yadav, Ravi
Background: There is a lack of clarity about the cognitive dysfunction in young patients with subclinical hypothyroidism (SCH). This study was done to explore the neuropsychological impairments in young patients with SCH and compare them with euthyroid controls. Methods: Patients between 18 and 45 years of age and diagnosed with SCH were recruited. Controls were euthyroid age, gender, and education matched. All the cases and controls underwent a detailed neuropsychological assessment with a battery of tests validated for use in the age groups of 18 to 65 years. Results: Thirty-nine patients with a mean age of 30.3 ± 7.7 years (female:male ratio 12:1) and 23 controls (female:male ratio 21:2) with a mean age of 33.4 ± 7.1 years ( P = .24) were included in the study. The mean TSH value was 6.36 ± 1.3 mIU/L and 2.49 ± 1.03 mIU/L in cases and controls, respectively ( P < .001). The visual memory delayed recall was impaired, in 48.71% ( n = 19) and 21.7% ( n = 5) cases and controls, respectively ( P = .03). The category fluency test showed impairment in a greater number of cases (35.9%, n = 14) as compared to controls (13%, n = 3; P = .04). Conclusion: This study shows that younger patients with SCH have delayed visual memory recall and category fluency deficits, which are suggestive of dysfunction of the prefrontal cortex and temporal lobe in young SCH patients. These impairments may justify the treatment of young SCH patients with replacement therapy.